Γραφές προσώπων, ίχνη παρουσίας: Σκέψεις πάνω σε κείμενα και φωτογραφίες από τις αρχές του 20ού αιώνα - Ιωαννίδης Κώστας (Σύγκριση/Comparaison/Comparison, 2023)
Writings of faces, traces of presence: Thoughts on texts and images from the early 20th century Working on photographs of prisoners and documents from the Smyrna Central Prison archive [High Commission of Smyrna (1919-1922)] I attempt a critical reflection on the application of theoretical and methodological tools such as art historical connoisseurship and attribution, tools originally developed to illuminate artistic production perceived as a vehicle of artistic expression, in order to discuss a material that is generally characterized as documentary since it is made up of artefacts that are supposed to refer neither to themselves nor to their creator as an artistic subject. Avoiding reductivism and the perpetuation of relations of hegemony of one medium over another or the artistic over the non-artistic, I attempt to make a contribution to the understanding of images and texts by pointing in the direction of coinherences, that is, showing that the conventional image-text, document-art work distinction is oversimplifying. Through a reading of the concept of the face in the text "La signification et le sens" by Emmanuel Levinas I discuss documentary images beyond the narrow confines of documentation, as ethically significant surfaces, and I highlight records within the archive that can be read, beyond the narrow confines of the bureaucratic routine of the prison, as indices of human presence.